Metal-organic framework (MOF)-incorporated polymeric electrolyte realizing fast lithium-ion transportation with high Li+ transference number for solid-state batteries - Xu, Yifan; Zhao, Ruo; Fang, Jianjun; Liang, Zibin; Gao, Lei; Bian, Juncao; Zhu, Jinlong; Zhao, Yusheng (Frontiers in Chemistry, 2022)
Composite polymer electrolytes (CPEs) show significant advantages in developing solid-state batteries due to their high flexibility and easy processability. In CPEs, solid fillers play a considerable effect on electrochemical performances. Recently, metal-organic frameworks (MOFs) are emerging as new solid fillers and show great promise to regulate ion migration. Herein, by using a Co-based MOF, a high-performance CPE is initially prepared and studied. Benefiting from the sufficient interactions and pore confinement from MOF, the obtained CPE shows both high ionic conductivity and a high Li+ transference number (0.41). The MOF-incorporated CPE then enables a uniform Li deposition and stable interfacial condition. Accordingly, the as-assembled solid batteries demonstrate a high reversible capacity and good cycling performance. This work verifies the practicability of MOFs as solid fillers to produce advanced CPEs, presenting their promising prospect for practical application.